KAJIAN BRAND IMAGE DAN BIAYA PENDIDIKAN TERHADAP KEPUTUSAN MEMILIH LEMBAGA BAHASA DI SUKABUMI - Rusli Nugraha (Universitas Bina Sarana Informatika Kota Sukabumi, 2015)
The presence of already well-known language institute in a town would be a new powerful competitor for the local language institution that already exists. Long-standing brand image on a national scale reinforces that the presence of this institution would be easy to get a lot of students. But in fact some of the local language institutions are not affected at all. They have no decline of student numbers. Another factor that is considered to determine the condition of this is the cost of education. This study aims to determine the influence of brand image and the cost of education to the student's decision in choosing a language institute.For education providers, the results of this study can be used as reference to determine the steps of promotion strategy.